Understanding levels of social economy development : an examination of Northern Canadian communities - McLean, Danielle (My University, 2009)
This study offers a preliminary analysis of the role specific social factors have on social economy development in the Yukon, Northwest Territories and Nunavut. Because of the marked differences in levels of social economy development in Northern Canadian communities, this research attempts to explain these variations through an examination of social variables that have been identified as impacting levels of development
Keywords: Economic development; Social aspects; Canada, Northern; Community development; Social capital (Sociology); Cooperative societies; Social economy